The manor estate economy ofthe Republic of Two Nations (the Polish-Lithuanian Commonwealth) in the 16th-18th centuries from the Marxist and neo-institutionalist perspectives - Žiemelis, Darius (Lietuvos istorijos studijos, 2011)
This article continues an analysis of the socioeconomic history of the Republic of Two Nations (RTN) in the 16th-18th centuries, viewed through two competing historiographical views: the traditional Marxist conception emphasizing internal considerations and the neo-Marxist capitalist world system theory (CWS) emphasizing external motivations. The questions addressed in this text arose from the conclusion of an earlier study (Lietuvos istorijos studijos, 2006, volume 18) that the agrarian structure of Eastern Europe in the 16th-18th centuries, according to the CWS conception, is similar in many respects to what Marxists call "feudalism" in Western Europe in the 11th-15th centuries (with the agrarian structure rather than political "superstructure" in mind). The point of this article is to define in more detail the structural similarities and differences between the Western European manor in the 11th-15th centuries and the Eastern European manor (especially in the RTN) in terms of Marxism and neo-institutionalism. In reconstructing the economic structure of the Western European manor from the Marxist perspective in the first section of the article, the author employs a research performed by the school of E. A. Kosminsky, a renowned medieval expert in the Soviet Union. American economists of the new institutionalist economic history work by its best-known representatives D. C. North and R. P. Thomas inform the neo-institutionalist perspective in the first section. In the second section, the model of feudal economic function by one of the most renowned Polish economic historians, W. Kula, is used for reconstructing the manor economy of Eastern Europe (and especially the RTN) in the 16th-18th centuries from the Marxist perspective. The third section features the above-mentioned studies as well as additional literature (J. Topolski, A. Wyczanski, P. Gorecki, K. Glamann, E. J. Hobsbawm, S. Pamerneckis and others), to illustrate in detail for the first time in historiography and expand upon, the structural similarities and differences between the Western European manor in the 11th-15th centuries and the Eastern European manor in the 16th-18th centuries according to both of the aforementioned perspectives. Arguments are put forward for the thesis that the manor economy of the 16th-18th centuries in the RTN, affected by Western Europe’s developing capitalist relationships, can be qualified neither as a typical feudal economy (which the Western European manor of the Middle Ages should properly be considered) nor as a typical capitalist enterprise. The RTN manor of the 16th-18th centuries was an economy based on the total domination by the lord of the peasants oriented to the production of mercantile goods, as one of the forms used by the lord for accumulating capital.